PERBANDINGAN KLASIFIKASI MUTU BATAKO PASIR PROGO, BATAKO PASIR OPAK DAN BATAKO PASIR MERAPI - Iskandar Yasin; Lilik Hendro; Afif Shulhan; Ibnu Kosim (RENOVASI : Rekayasa Dan Inovasi Teknik Sipil, 2026)
Batako is usually used in the pavement of an area. Bricks are made with a mixture of cement, water and fine aggregate without additives. Batako has its own standard quality level to determine the use and function of the brick. The standard is contained in SNI 03-0349-1989. Where Batako is divided into 4 classifications, namely Quality Level I, Quality Level II, Quality Level III, and Quality Level IV. The calcification is obtained from the compressive strength value of a brick. Therefore, this research was conducted to examine the strength comparison of compressive strength values between Progo sand brick, Opak sand brick and Merapi sand brick. This study used experimental research methods in the laboratory using 3 test objects, each of which was represented by 3 samples. So that the total test object used is 9 pieces of test object. object 1 is Progo sand brick, object 2 is Opak sand brick and object 3 is Merapi sand brick. The test results show that Progo sand brick has an average strength value of 19.333 MPa, Opak sand brick has a compressive strength value of 27 MPa. Meanwhile, Merapi sand brick has a compressive strength value of 37 MPa. Keywords: Progo Sand Bricks, Opak Sand Bricks, Merapi Sand Bricks